Photon-counting detector CTA to assess intracranial stents and flow diverters: an in vivo study with ultrahigh-resolution spectral reconstructions - Frederic De Beukelaer; Sophie De Beukelaer; Laura L. Wuyts; Omid Nikoubashman; Mohammed El Halal; Iliana Kantzeli; Martin Wiesmann; Hani Ridwan; Charlotte S. Weyland (European Radiology Experimental)
Abstract Background To define optimal parameters for the evaluation of vessel visibility in intracranial stents (ICS) and flow diverters (FD) using photon-counting detector computed tomography angiography (PCD-CTA) with spectral reconstructions. Methods We retrospectively analyzed consecutive patients with implanted ICS or FD, who received a PCD-CTA between April 2023 and March 2024. Polyenergetic, virtual monoenergetic, pure lumen, and iodine reconstructions with different keV levels (40, 60, and 80) and reconstruction kernels (body vascular [Bv]48, Bv56, Bv64, Bv72, and Bv76) were evaluated by two radiologists with regions of interests and Likert scales. Reconstructions were compared in descriptive analysis. Results In total, twelve patients with nine FDs and six ICSs were analyzed. In terms of quantitative image quality, sharper kernels as Bv64 and Bv72 yielded increased image noise and decreased signal-to-noise and contrast-to-noise ratios compared to the smoothest kernel Bv48 (p = 0.001). Among the different keV levels and kernels, readers selected the 40 keV level (p = 0.001) and sharper kernels (in the majority of cases Bv72) as the best to visualize the in-stent vessel lumen. Assessing the different spectral reconstructions virtual monoenergetic and iodine reconstructions proved to be best to evaluate in-stent vessel lumen (p = 0.001). Conclusion PCD-CTA and spectral reconstructions with sharper reconstruction kernels and a low keV level of 40 seem to be beneficial to achieve optimal image quality for the evaluation of ICS and FD. Iodine and virtual monoenergetic reconstructions were superior to pure lumen and polyenergetic reconstructions to evaluate in-stent vessel lumen. Relevance statement PCD-CTA offers the opportunity to reduce the need for invasive angiography serving as follow-up examination after intracranial stent (ICS) or flow diverter (FD) implantation. Key Points Neuroimaging of intracranial vessels with implanted stents and flow diverters is limited by artifacts. Twelve patients with nine flow diverters and six intracranial stents underwent photon-counting detector computed tomography angiography (PCD-CTA). In-stent vessel lumen visibility improved using sharp reconstruction kernels and a low keV level. Virtual monoenergetic and iodine reconstructions were best to evaluate in-stent vessel lumen. Graphical Abstract